Estimation of Government Health Expenditures in Iran During 2006 to 2011, Using Panel Data. Issue 1 (January 2019) - Ravangrad, Ramin; Shahnazi, Rouhollah; Karimi, Fereshteh; Jafari, Abdosaleh; Shokrpour, Nasrin
Abstract : The status of public resources in health has a positive and direct impact on this sector's outcomes because of its effect on the increase of social services. The government's ability to manage health expenditures greatly depends on identifying the determinants of these expenditures. Therefore, this study aimed to determine factors affecting the government health expenditures and estimate the related function in Iran during 2006-2011 using panel data. This was a cross-sectional and time-series study that was conducted using panel data analysis. In this study, the data were collected and categorized separately for each province from documents in the Ministry of Health and the Statistical Center of Iran. The results showed that there were positive associations between health expenditures and some factors including age group of 20 to 39 years ( P = .04), the number of women ( P = .001), the number of physicians, the number of hospital beds, and annual budget ( P < .001). According to the results, it seems that allocating a part of health subsidies for increasing the insurance coverage of the age group of 20 to 39 years and also starting saving accounts can have an important effect on reducing health expenditures of this age group.